2021
DOI: 10.4103/jpgm.jpgm_793_20
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-induced large duct cholangiopathy

Abstract: Immune-checkpoint inhibitor mediated hepatobiliary injury is an emerging concern in cancer treatment. Most of these adverse reactions are attributed to nivolumab and are characterized by panlobular hepatitis. Large duct cholangiopathy related to these drugs is extremely rare. We present a case of adenocarcinoma of lung treated with pembrolizumab who developed biochemical and imaging features consistent with cholangiopathy characterized by common bile duct dilatation, wall enhancement, and gallbladder wall edem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…15 Large duct changes were reported in association with pembrolizumab and nivolumab. 16,17 One study found radiological features of cholangiopathy in two patients treated with pembrolizumab, with a third demonstrating primary biliary cholangitis-like changes histologically. 18 Other biliary features have included noninfective cholangitis with predominant neutrophilic or lymphocytic infiltrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Large duct changes were reported in association with pembrolizumab and nivolumab. 16,17 One study found radiological features of cholangiopathy in two patients treated with pembrolizumab, with a third demonstrating primary biliary cholangitis-like changes histologically. 18 Other biliary features have included noninfective cholangitis with predominant neutrophilic or lymphocytic infiltrates.…”
Section: Introductionmentioning
confidence: 99%
“…Doherty et al reported three cases of severe liver injury associated with biliary changes that were refractory to therapy, including a ‘disappearing bile duct’ phenotype 15 . Large duct changes were reported in association with pembrolizumab and nivolumab 16,17 . One study found radiological features of cholangiopathy in two patients treated with pembrolizumab, with a third demonstrating primary biliary cholangitis‐like changes histologically 18 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Although ICIs can cause immune-related adverse reactions (IRAEs), 9 the IRAE frequency is low. However, malnutrition due to colitis with severe diarrhea, pericarditis, 10 hepatotoxicity, 11 and circulatory disturbance due to IRAEs to lower extremity soft tissue are reported causes of BLE. 12,13 Many patients who develop IRAEs recover with corticosteroids.…”
Section: Introductionmentioning
confidence: 99%